Розвяжіть рівняння1 х-44х+6=х-5²2 3х²-6х _=4-2х 2

Розвяжіть рівняння

1) (х-4)(4х+6)=(х-5)²

2) 3х²-6х

  _________=4-2х

         2

    2) 3х^2-6х

           x=--------

        

         3x^2-6x=2(4-2x)

          3x^2=49

               1+-√1+24

             2

     

      ----------- = 4-2х          |*2

         4x^2+6x-16x-24=x^2-10x+25

          3x^2-6x+4x-8=0

  • 1) (х-4)(4х+6)=(х-5)^2

            x=---------

                        3

           x^2=49/3

       Ответ:2, -4/3

            x=2

                     3

           x=--------

                  √3

            x=-4/3

         4x^2-10x-24=x^2-10x+25

                 1+-5

          3x^2-49=0

                 7√3

                     3

          4x^2-x^2-10x+10x-24-25=0

                  7

          3x^2-6x=8-4x

          3x^2-2x-8=0

           x=--------------